Analysis of oxy-fuel combustion as an alternative to combustion with air in metal reheating furnaces - Oliveira, Flavio Augusto Dias de [UNESP]; Carvalho Junior, João Andrade de [UNESP]; Magalhães Sobrinho, Pedro [UNESP]; Castro, André de [UNESP] (Elsevier B.V., 2014)
Using oxygen instead of air in a burning process is at present being widely discussed as an option to reduce CO2 emissions. One of the possibilities is to maintain the combustion reaction at the same energy release level as burning with air, which reduces fuel consumption and the emission rates of CO2. A thermal simulation was made for metal reheating furnaces, which operate at a temperature in the range of 1150-1250 degrees C, using natural gas with a 5% excess of oxygen, maintaining fixed values for pressure and combustion temperature. The theoretical results show that it is possible to reduce the consumption of fuel, and this reduction depends on the amount of heat that can be recovered during the air pre-heating process. The analysis was further conducted by considering the 2012 costs of natural gas and oxygen in Brazil. The use of oxygen showed to be economically viable for large furnaces that operate with conventional heat recovering systems (those that provide pre-heated air at temperatures near 400 degrees C). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Oxy-fuel combustion; Fuel consumption; Reheating furnaces